Forecasting the export competitiveness of Peruvian coffee in major importing countries usingautoregressive integrated moving average modeling - Abanto Duran, Roger Francisco (2024)
The study analyzes the export competitiveness of Peruvian coffee in international markets using the ARIMA model to forecast export trends. The objective is to identify factors influencing the sector's profitability and sustainability. Time series of export volumes and prices were evaluated, revealing that the ARIMA model allows for accurate predictions of future trends. The results suggest that the Peruvian coffee sector faces challenges related to international price fluctuations and global competition. Emphasis is placed on the importance of efficiency in production and export processes to maintain and enhance the competitiveness of Peruvian coffee in the global market.